Identification of Drosophila type II neuroblast lineages containing transit amplifying ganglion mother cells. - Boone, J.Q.; Doe, C.Q. (Developmental Neurobiology, 2008)
Mammalian neural stem cells generate transit amplifying progenitors that expand the neuronal population, but these type of progenitors have not been studied in Drosophila. The Drosophila larval brain contains approximately 100 neural stem cells (neuroblasts) per brain lobe, which are thought to bud off smaller ganglion mother cells (GMCs) that each produce two post-mitotic neurons. Here, we use molecular markers and clonal analysis to identify a novel neuroblast cell lineage containing "transit amplifying GMCs" (TA-GMCs). TA-GMCs differ from canonical GMCs in several ways: each TA-GMC has nuclear Deadpan, cytoplasmic Prospero, forms Prospero crescents at mitosis, and generates up to 10 neurons; canonical GMCs lack Deadpan, have nuclear Prospero, lack Prospero crescents at mitosis, and generate two neurons. We conclude that there are at least two types of neuroblast lineages: a Type I lineage where GMCs generate two neurons, and a type II lineage where TA-GMCs have longer lineages. Type II lineages allow more neurons to be produced faster than Type I lineages, which may be advantageous in a rapidly developing organism like Drosophila.